Relativistic theory of low energy electron diffraction - Feder, Roland (Department of Physics, 2016)
In view of investigating the role of spin polarization and further relativistic effects in the diffraction of low energy electrons (LEED) by crystals composed of heavy atoms, a relativistic dynamical theory is developed for calculating LEED intensities and spin polarizations. The presentation of the general framework of solving the boundary value problem for the mixed-representation Dirac equation is followed by the construction of a relativistic KKRZ-type electron-ion-core pseudopotential. The solution of the Dirac equation inside a model crystal that consists of this potential plus a bulk and surf ace optical potential is then derived in an algebraic form. Provision is made for taking into account thermal lattice effects. The computational application of this relativistic LEED theory to the (ool) and the (llo) surface pf tungsten firstly yields intensity results that are found to be in good agreement with experimental data. Secondly, appreciable spin polarization features are predicted, in particular in the specular beam for large angles of incidence on W(ool) at very low energies. It is concluded that measurement of spin polarization in LEED can be expected to be a valuable tool for obtaining additional information about the surface region.